Faktor-Faktor yang Mempengaruhi Kemandirian Keuangan Daerah pada Kabupaten/Kota di Wilayah Provinsi Kalimantan Selatan Tahun 2007-2016 - Utami, Maulida (PPJP ULM, 2018)
This research aims to see how Local Own Revenue, Gross Domestic RegionalProduct and General Allocation Funds on the Financial Self Sufficiency inRegency/Cities in South Kalimantan Province. The population of this study is 13Regency/Cities in South Kalimantan during 2007-2016.This research is descriptive and quantitative and using secondary dataobtained by DJPK and BPS. Analysis technique with multiple linear regression analysismethods.The results of this study indicate that Local Own Revenue impact a positiveeffect, Gross Domestic Regional Product did not affect, and General Allocation Fundsimpact a negative impact on the level of Financial Self Sufficiency. Regions with miningmainstay sectors have low Financial Self Sufficiency while areas with non-miningmainstay sector have a high Financial Self Sufficiency